STUDI KARAKTERISTIK JAGUNG INTRODUKSI DAN BEBERAPA VARIETAS JAGUNG LOKAL - Ahmad Amrin S (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2021)
The aims of this research to known the characteristics of vegetative and generative introduction of maize and local maize varieties. The research was conducted at UPT Balai Benih Induk (BBI) of Palawija Agricultural Department of Tanjung Selamat, Medan Sunggal, Deli Serdang District in August to November 2017. This research used non factorial Randomized Block Design (RDB) with 3 varieties: Purple maize, Bonanza and Pioneer. The observed parameters were plant height, age of male flowering, age of female flowering, harvest age, crop production per plot, length of corncob, number of rows per corncob, weight of 100 seeds and heritability. The result showed had significant effect of plant height (8 weeks after planting) and weight of crop production per plot. The observed heritability value of the parameters showed high criteria.